2009
DOI: 10.1007/s11033-009-9737-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resveratrol on cyclooxygenase-1 and cyclooxygenase-2 mRNA and protein levels in diabetic rat kidneys

Abstract: Cyclooxygenase (COX), which have the isoforms of COX-1 and COX-2, is the key enzyme of prostaglandins biosynthesis. Especially, COX-2 is induced in inflammatory disease such as Diabetes Mellitus (DM). Resveratrol (RSV), a natural antioxidant, has a beneficial role in prevention of inflammatory disease. We investigated the changes of COX-1 and COX-2 mRNA expression and protein level in diabetic rat kidney after RSV treatment. Three months-old, 44 Wistar albino male rats, which were divided into six groups such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…However, our studies also demonstrate further increase in COX-2 expression after highglucose exposure and ANG II. Moreover, the glomerular and cortical expression of COX-2 is increased in animal models of diabetes, suggesting that COX-2 plays an important role in the pathogenesis of diabetic nephropathy (23,24,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, our studies also demonstrate further increase in COX-2 expression after highglucose exposure and ANG II. Moreover, the glomerular and cortical expression of COX-2 is increased in animal models of diabetes, suggesting that COX-2 plays an important role in the pathogenesis of diabetic nephropathy (23,24,45).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer, antioxidant, antifungal infection, anti-inflammatory activity, antiplatelet activity, pro-apoptotic and cardioprotective properties of resveratrol have been well established recently. [12][13][14][15] The purpose of the this study was to investigate the effects of melatonin, quercetin and resveratrol on hepatocellular injury in STZ-induced diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Although RSV is thought to be a specific inhibitor of COX-1 (Szewczuk et al, 2004), at high concentrations it has been reported to reduce basal COX-2 activity in vitro (Jang et al, 1997). Our previous study demonstrated that RSV reduced COX-2 and especially COX-1 mRNA level but there were no statistically significant differences between DM and DM+RSV groups in STZ-induced DM rat kidney tissue (P > 0.05) (Yar et al, 2010). Similarly, RSV reduced the COX-1 mRNA level in STZ-induced DM rat heart tissues in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…All animals were acclimatized for a minimum period of 1 week prior to the beginning of the study. Forty-four 3-month-old, Wistar albino male rats were used for the study as described previously (Yar et al, 2010). Animals were randomly divided into 6 experimental groups [group I: nondiabetic rats used as a control group (N = 6); group II: sodium citrate buffer control group (sham control; N = 7); group III: STZ-induced diabetic group (DM; N = 9); group IV: DMSO-induced control group (DMSO; N = 6); group V: RSV-treated sham control group (RSV; N = 7); group VI: RSV-treated diabetic group (DM+RSV; N = 9)].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation